Anti-inflammatory and antipyretic activity of Fioria vitifolia - Mahalakshmi, Krishnamoorthi; Natesan, Senthil Kumar; Parthiban, Kugalur ganesan; Sekar, Ganesan (International Current Pharmaceutical Journal, 2013)
Fioria vitifolia Linn., (Malvacae) has been extensively used in folk medicine for the treatment of common cold, flu, and upper respiratory infections and also as an immune system booster. Steroids, flavonoids, and triterpenes, gossypin alkaloids have been isolated from the whole part of the plant. In the present study, the methanolic extract of dried plant of Fioria vitifolia (MEFV) was investigated for anti-inflammatory (carrageenan induced rat paw oedema) and anti-pyretic (brewers yeast induced pyrexia) activities. Pre-treatment with the extract (250-500mg/ kg, p. o) significantly prevented increase in volume of paw oedema in dose dependent manner. A maximal effect was observed at 500mg/kg which was comparable to diclofenac (20mg/kg, orally). Ceiling effect at the dose of 500mg/kg was observed. The anti-pyretic effect of MEFV (measured as % reduction in body temperature) was compared with paracetamol (150mg/kg, orally). MEFV in dose of 500mg/kg caused significant decrease in body temperature of rats. In conclusion, this study has established the anti-inflammatory activity and anti pyretic activity of Fioria vitifolia and thus, justifies the ethnicuses of the plant. DOI: http://dx.doi.org/10.3329/icpj.v2i7.15154 International Current Pharmaceutical Journal, June 2013, 2(7): 119-121